ENCHANCING CUSTOMER PURCHASE DECISION THROUGH BRAND IMAGE, TRUST AND INSTAGRAM DIGITAL MARKETING : A CASE STUDY OF PT. DHARMAJAYA KIMIA PRATAMA - Stefanie Angelica Jerico; Rifin Khong (Faculty of Economics and Business Universitas Pelita Harapan, 2025)
Dharmajaya Kimia Pratama experienced a decline in customer purchase decisions which resulted in decreased sales data caused by brand image, trust, and instagram digital marketing. The Objective Research that will be used can be describe to analyze whether the brand image, trust, and instagram digital marketing have partial and simultaneous effect toward customer purchase decision at PT. Dharmajaya Kimia Pratama. Brand image, trust, and instagram digital marketing play an important role in increasing customer purchase decisions and sales. In this research, the writer used quantitative, descriptive, causal research design. The sampling technique used was convenient sampling. The sample size was 140 customers at PT. Dharmajaya Kimia Pratama. The data analysis technique uses multiple linear regression analysis with the SPSS program. The results of hypothesis test showed that brand image, trust, and instagram digital marketing have partial and simultaneous effect toward customer purchase decision at PT. Dharmajaya Kimia Pratama and adjusted R square value of 52.1%. Recommendations for PT. Dharmajaya Kimia Pratama need to be more active in utilizing Instagram as a promotional media and introducing products, organize uploading content regularly and consistent in the use of raw materials in accordance with the composition.